Jacaranone Derivatives with Antiproliferative Activity from Crepis pulchra and Relevance of This Group of Plant Metabolites - Csilla Zsuzsanna Dávid; Norbert Kúsz; Gyula Pinke; Ágnes Kulmány; István Zupkó; Judit Hohmann; Andrea Vasas (Plants, 2022)
Jacaranones are a small group of specific plant metabolites with promising biological activities. The occurrence of jacaranones is limited to only a few plant families, with Asteraceae being the most abundant source of these compounds. Therefore, jacaranones can also serve as chemotaxonomic markers. Our phytochemical investigation of Crepis pulchra L. (Asteraceae) resulted in three jacaranone derivatives (jacaranone, 2,3-dihydro-2-hydroxyjacaranone, 2,3-dihydro-2-methoxyjacaranone), and (6R,9S)-3-oxo-α-ionol-β-d-glucopyranoside, fulgidic acid, 12,15-octadecadienoic acid methyl ester, scopoletin and apigenin-7-O-β-d-glucoside. This is the first report on the isolation of jacaranones from a species belonging to the Cichorioideae subfamily of Asteraceae. Jacaranone derivatives were subjected to an in vitro antiproliferative assay against a panel of human cancer cell lines (MCF-7, MDA-MB-231, HeLa, and C33A), revealing high or moderate activities, with IC50 values ranging from 6.3 to 26.5 μM.